Induced radioactivity in AB-BNCT: an analysis of the different facilities worldwide - Capoulat, M. E.; Kreiner, A. J. (Frontiers in Nuclear Engineering, 2023)
The global effort to establish Accelerator-Based Boron Neutron Capture Therapy (AB-BNCT) facilities involves various accelerator technologies and neutron-producing targets, each characterized by different properties of the primary beam and neutron spectra they generate. With an emphasis on long-term sustainability, it is essential to minimize the production of residual radioactivity to the lowest possible level, particularly given their intended use in a hospital environment. This paper aims to quantitatively assess the residual radioactivity in these facilities, taking into account both primary and secondary activation. Primary activation primarily arises from the interaction of the proton or deuteron beam and the neutron-producing target. Secondary activation results from neutron-induced reactions on the elements exposed to the neutron flux, with the Beam Shaping Assembly (BSA) being the most exposed one. To assess activation, we evaluated a representative group of target-BSA configurations. Primary activation was calculated based on cross-sectional data and the corresponding target materials. Neutron activation was assessed using Monte Carlo simulations with the MCNP 6.1 code. Regarding target activation, our findings indicate that 9Be targets working with protons of less than 10 MeV represent the cleanest option, while 7Li targets working with protons lead to the highest activation levels. As for BSA activation, the neutron energy is a crucial factor. In the case of standard BSA materials, higher neutron energy results in an increased number of potential reactions that produce radioactive products. Additionally, our findings suggest that radioactivity induced by impurities and minor components in alloyed materials cannot be disregarded and must be taken into account in radioactivity calculations. In summary, this research provides a comprehensive analysis of activation of the commonly used targets and BSA materials, aimed at contributing to the optimization of AB-BNCT facilities from a radiological perspective.